An analytical investigation of alternative batching policies for remanufacturing under stochastic demands and returns. (16th June 2021) - Zhang, Yi; Akçalı, Elif; Çetinkaya, Sıla
Abstract: This article examines a fundamental lot-sizing problem which arises in the context of a make-to-order remanufacturing environment. The problem setting is characterized by a stochastic used-item return process along with a stochastic remanufactured-item demand process faced by a remanufacturer. We explicitly take into account for all relevant costs, including the fixed costs (associated with remanufacturing of used-items and dispatching of remanufactured-item orders in batches) and inventory-related cost (associated with used-item inventory holding costs and remanufactured-item order waiting costs). We propose five batching policies inspired by shipment consolidation practice (three periodic policies and two threshold policies). For the purpose of computing policy parameters, we develop analytical models that are aimed at minimizing the long-run average expected total cost of the remanufacturer. Since the underlying cost expressions are not analytically tractable, we propose easily computable approximations that lead to closed-form expressions for obtaining policy parameters. A careful numerical investigation demonstrates that the resulting policy parameters are highly effective approximations. Then, we extend the policies by considering disposal options when needed. For this extension, an effective parameter-based approximation approach is developed for computational purposes, and additional numerical experiments demonstrate the effectiveness of the proposed approach.